White matter tractography for neurosurgical planning: A topography-based review of the current state of the art - Essayed, Walid I.; Zhang, Fan; Unadkat, Prashin; Cosgrove, G. Rees; Golby, Alexandra J.; O'Donnell, Lauren J. (NeuroImage clinical, 2017)
We perform a review of the literature in the field of white matter tractography for neurosurgical planning, focusing on those works where tractography was correlated with clinical information such as patient outcome, clinical functional testing, or electro-cortical stimulation. We organize the review by anatomical location in the brain and by surgical procedure, including both supratentorial and infratentorial pathologies, and excluding spinal cord applications. Where possible, we discuss implications of tractography for clinical care, as well as clinically relevant technical considerations regarding the tractography methods. We find that tractography is a valuable tool in variable situations in modern neurosurgery. Our survey of recent reports demonstrates multiple potentially successful applications of white matter tractography in neurosurgery, with progress towards overcoming clinical challenges of standardization and interpretation. •We review state-of-the-art white matter tractography for surgical planning.•Review is organized by anatomical location in the brain and by surgical procedure.•Clinically relevant technical considerations are provided.•Tractography is a valuable tool in variable situations in modern neurosurgery.